No such thing as Nessie! - McBain, Chani (Picture Kelpies/Floris Books, 2013)
Nessie...obsessed Finlay is determined to prove the famous Loch Ness Monster really does exist. Gran might believe him but his big sister Sarah keeps telling him there's no such thing. But is that a monster-ish shape under the water? There's no such thing as Nessie: is there?